PENGARUH PEMBERIAN BEBERAPA TAKARAN BIOCHAR SEKAM PADI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PAKCOY (Brassica rapa L.) - Ramadona, Putri; Yusnaweti, Yusnaweti; Sumbari, Chika (Ensiklopedia of Journal, 2024)
The study entitled "The Effect of Applying Several Doses of Rice Husk Biochar on the Growth and Yield of Pakcoy Plants (Brassica rapa L.)"  has been carried out in the experimental garden of the Faculty of Agriculture, University of Muhammadiyah West Sumatra, Tanjung Gadang Koto Nan Ampek Village, West Payakumbuh District, Payakumbuh city, with the type of Inseptisol soil, the altitude of the place ± 514 meters above sea level. This research was conducted from March 2024 to June 2024.This experiment uses a Group Random Design (RAK) with 5 treatments and 4 groups, so that there are 20 plots in total.  In 1 plot there are 16 plants and 3 of them are randomly selected sample plants. The treatment is the application of Rice Husk Biochar with a dosage of 0 tons/ha, 20 tons/ha, 25 tons/ha, 30 tons/ha and 35 tons/ha.  The data from the observation results were averaged and analyzed statistically with the F test at a real level of 5 % if F is calculated large from the F table, then it is followed by the Duncan's New Multiple Range Test (DNMRT) test at a real level of 5 %. This study uses a Group Random Design (RAK) with 5 treatments and 4 groups, so that there are 20 plots in total.  In 1 plot there are 16 plants and 3 of them are randomly selected sample plants. The treatment is the application of Rice Husk Biochar with a dosage of 0 tons/ha, 20 tons/ha, 25 tons/ha, 30 tons/ha and 35 tons/ha.  The data from the observation results were averaged and analyzed statistically with the F test at a real level of 5 % if F is calculated large from the F table, then it is followed by the Duncan's New Multiple Range Test (DNMRT) test at a real level of 5 %.The results of the study can be concluded that the application of Rice Husk Biochar at a dose of 35 tons/ha provides the best response to the growth and yield of Pakcoy plants.Keywords: Rice Husk Biochar, Pakcoy Plants, Growth and Yield